Positron emission tomography assessment of 8-OH-DPAT-mediated changes in an index of cerebral glucose metabolism in female marmosets - Converse, Alexander K.; Aubert, Yves; Farhoud, Mohammed; Weichert, Jamey P.; Rowland, Ian J.; Ingrisano, Nicole M.; Allers, Kelly A.; Sommer, Bernd; Abbott, David H. (NeuroImage (Orlando, Fla.), 2012)
As part of a larger experiment investigating serotonergic regulation of female marmoset sexual behavior, this study was designed to (1) advance methods for PET imaging of common marmoset monkey brain, (2) measure normalized FDG uptake as an index of local cerebral metabolic rates for glucose, and (3) study changes induced in this index of cerebral glucose metabolism by chronic treatment of female marmosets with a serotonin 1A receptor (5-HT1A) agonist. We hypothesized that chronic treatment with the 5-HT1A agonist 8-OH-DPAT would alter the glucose metabolism index in dorsal raphe (DR), medial prefrontal cortex (mPFC), medial preoptic area of hypothalamus (mPOA), ventromedial nucleus of hypothalamus (VMH), and field CA1 of hippocampus. Eight adult ovariectomized female common marmosets (Callithrix jacchus) were studied with and without estradiol replacement. In a crossover design, each subject was treated daily with 8-OH-DPAT (0.1mg/kg SC daily) or saline. After 42–49days of treatment, the glucose metabolism radiotracer FDG was administered to each female immediately prior to 30min of interaction with her male pairmate, after which the subject was anesthetized and imaged by PET. Whole brain normalized PET images were analyzed with anatomically defined regions of interest (ROI). Whole brain voxelwise mapping was also used to explore treatment effects and correlations between alterations in the glucose metabolism index and pairmate interactions. The rank order of normalized FDG uptake was VMH/mPOA>DR>mPFC/CA1 in both conditions. 8-OH-DPAT did not induce alterations in the glucose metabolism index in ROIs. Voxelwise mapping showed a significant reduction in normalized FDG uptake in response to 8-OH-DPAT in a cluster in medial occipital cortex as well as a significant correlation between increased rejection of mount attempts and reduced normalized FDG uptake in an overlapping cluster. In conclusion, PET imaging has been used to measure FDG uptake relative to whole brain in marmoset monkeys. Voxelwise mapping shows that 8-OH-DPAT reduces this index of glucose metabolism in medial occipital cortex, consistent with alterations in female sexual behavior. ► Methods advanced for PET imaging of marmoset brain. ►Normalized FDG uptake observed during control saline treatment. ► Chronic treatment with 8-OH-DPAT reduced this metabolism index in occipital cortex.